Intеllectual Migration to Israel: the Russian Aspect - V. M. Morozov (Vestnik MGIMO-Universiteta)
The article is dedicated to studying the factor of intellectual emigration from Russia to Israel. Historical preconditions are examined, and its various tendencies in different times are learned. The author tries to analyze “brain drain” from Russia to Israel and gives recommendations on formulating Russian state policy for the purpose of current Russian intellectual migration flow to Israel reduction.